Strategi Pemerintah yang Efektif dalam Menangani Dampak Perubahan Iklim di Wilayah Papua Barat: Optimalisasi Anggaran untuk Mitigasi dan Adaptasi - Wurarah, Rully; Mulyanto (Jurnal Bina Praja, 2024)
Climate change is a global challenge that significantly impacts various environmental, economic, and social sectors. In the West Papua region, the effects of climate change are increasingly being felt, especially in the agriculture, fisheries, and local ecosystem sustainability sectors. Local governments play an important role in developing effective mitigation and adaptation strategies to face this challenge. This research aims to analyze the budget optimization strategies used by local governments to address the impacts of climate change in the region. This research uses a qualitative approach with a case study method to examine local government policies on climate change. Data were obtained through focus group discussions with government officials, analysis of policy documents, and analysis of budget data. The Miles and Huberman interactive model was used in the analysis, which involved data collection, reduction, presentation, and conclusion drawing. The results showed significant budget allocations for climate change mitigation and adaptation changes between 2023 and 2024. The budget for mitigation decreased by 39.70%, while the budget for adaptation increased by 62.86%. The decrease in the mitigation budget reflects efficiencies that have been achieved or changes in priorities. In contrast, the increase in the adaptation budget indicates an increased focus on community and infrastructure resilience to climate change impacts. Priority action plans identified in this study include strengthening climate-resilient infrastructure, water and waste management, renewable energy development, increasing community capacity and participation, diversifying funding sources, and technology development and application. Recommendations for local governments emphasize the importance of continuous evaluation, inclusive policy development, collaboration with the private sector, and increased public awareness and participation in dealing with climate change.